Chosen problems and socially-economical dilemmas of the valuation of relation between human and natural environment - Rudnicki, Maciej (Studia Ecologiae et Bioethicae, 2007)
In this article autor shows the relation between human and natural environment and the chosen problems connected with this especially social, technological, economical with ecological and law problems and dilemmas connected with ecological safety of the human and the whole biosphere.